2015
DOI: 10.4313/teem.2015.16.6.312
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hard Mask for Finer (<10 μm) Through Silicon Vias (TSVs) Etching

Abstract: Through silicon via (TSV) technology holds the promise of chip-to-chip or chip-to-package interconnections for higher performance with reduced signal delay and power consumption. It includes high aspect ratio silicon etching, insulation liner deposition, and seamless metal filling. The desired etch profile should be straightforward, but high aspect ratio silicon etching is still a challenge. In this paper, we investigate the use of etch hard mask for finer TSVs etching to have clear definition of etched via pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Traditional PR mask resulted in collapsed scallop patterns with smaller CDs. Choi and Hong [5] compared the etching results with PR and SiO 2 masks during fabrication of small structures. They found that SiO 2 hard mask provided better Si etch rate and smoother sidewalls compared to the PR mask.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional PR mask resulted in collapsed scallop patterns with smaller CDs. Choi and Hong [5] compared the etching results with PR and SiO 2 masks during fabrication of small structures. They found that SiO 2 hard mask provided better Si etch rate and smoother sidewalls compared to the PR mask.…”
Section: Introductionmentioning
confidence: 99%
“…For specific TSV applications, 97,98) the use of an organic resist instead of an inorganic hardmask (e.g. SiO 2 ) as masking material for deep RIE is preferred, since it minimizes the number of process steps and can be easily stripped in situ.…”
Section: Moore's Law 20mentioning
confidence: 99%
“…CO 2 , COS, O 2 , C 4 F 8 , SF 6 , Ar etc., are usually used during hard mask etching. [8][9][10] Main etching (ME) is the reaction of C 4 F 8 , C 4 F 6 , O 2 , Ar, NF 3 with SiO 2 film. [11][12][13] The fluorine plasmas (F * ) dissociated by fluorocarbons and hydrofluorocarbons can react with ARC to generate gas then volatilize.…”
mentioning
confidence: 99%